2020
DOI: 10.3168/jds.2019-17550
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Cocoa husks can effectively replace soybean hulls in dairy sheep diets—Effects on milk production traits and hematological parameters

Abstract: The aim of this study was to test the effect of replacing soybean hulls with different doses of cocoa husk (CH) on milk production traits and the hematological profile of dairy ewes. Twenty-four mid-lactating Sarda dairy ewes were allotted to 3 homogeneous experimental groups (8 animals per group divided into 4 pens). Each group received a total mixed ration as a basal diet and a supplement that differed among groups. The first group was supplemented with 100 g of soybean hulls/d per head (SBH group). In the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
2
12
0
2
Order By: Relevance
“…Some reports about V. patens leaves demonstrate antifungal activity associated with the pentacyclic triterpenoid lupeol [ 13 , 31 ]. The cocoa husk is the principal by-product of the cocoa agroindustry which still contains a high nutritional value [ 32 ]. Major bioactive compounds identified in cocoa husk are phenols, theobromine, caffeine, procyanidins, and catechins [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports about V. patens leaves demonstrate antifungal activity associated with the pentacyclic triterpenoid lupeol [ 13 , 31 ]. The cocoa husk is the principal by-product of the cocoa agroindustry which still contains a high nutritional value [ 32 ]. Major bioactive compounds identified in cocoa husk are phenols, theobromine, caffeine, procyanidins, and catechins [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cocoa shells' soluble dietary fiber promotes health beneficial effects on the regulation of cholesterol levels and reducing food intake and body weight gain [ 34 ]. Other studies have reported health protective effects on lipid and glucose metabolism and oxidative stress [ 32 ]. In a study with experimental animals, the cocoa soluble fiber from cocoa shells favorable changes of weight, insulinemia, lipids, glycemia, and blood pressure for the treatment of metabolic syndrome diseases [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, experimental data on theobromine carry over in milk are not available, as well as the metabolic effects of cocoa husks diet supplementation. In a previous work, milk and blood parameters of ewes supplemented with different doses of cocoa husks were evaluated [5]. In this experiment DMI and milk yield were not affected; however, milk protein content increased with cocoa husk supplementation.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, the cocoa husks supplementation lowered milk somatic cell count (SCC), suggesting a beneficial role of these by-products on mammary health status. Both systemic and local health conditions were good as evidenced by hematological parameters and electrophoretic profile of serum protein fractions [5]. Both systemic and local health conditions were good as evidenced by hematological parameters and electrophoretic profile of serum protein fractions [5].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation